APLIKASI RHIZOBIUM SEBAGAI SUMBER NITROGEN BAGI PERTUMBUHAN TANAMAN - Husnul Jannah (Bioscientist : Jurnal Ilmiah Biologi, 2015)
Rhizobium in Legum plants can be used as a source of Nitrogen. The roots of Legum plant roots are roots that contain rhizobium bacteria as nitrogen fixing which can be used as a source of nitrogen growth. The purpose of this study was to determine the utilization of peanut root nodules (Arachis hypogaea) as a source of Nitrogen in the growth of cayenne pepper seeds (Capsicum frutescens). This research includes pure experimental research. The design used is a Completely Randomized Design (CRD). Data collection techniques in this study used observation and documentation techniques. While the data analysis technique uses Anova One Way. This study consisted of J treatments namely P.Q (KQ11tml with 100% soil), PJ (1.5 grams of peanut root nodules), P.2 (3 grams of peanut root nodules) and repeated 4 times. The parameters observed in this study were plant height, number of leaves, and total leaf area.